Diffusion Tensor Imaging And Tractography In Autistic, Dysphasic, And Healthy Control Children - Hrdlicka M (Dove Medical Press, 2019)
Michal Hrdlicka,1 Jan Sanda,2 Tomas Urbanek,3 Martin Kudr,4 Iva Dudova,1 Stepanka Kickova,1 Lenka Pospisilova,1,5 Marketa Mohaplova,1 Alice Maulisova,4 Pavel Krsek,4 Martin Kyncl,2 Marek Blatny,1,6 Vladimir Komarek4 1Department of Child Psychiatry, Charles University Second Faculty of Medicine and University Hospital Motol, Prague, Czech Republic; 2Department of Radiology, Charles University Second Faculty of Medicine and University Hospital Motol, Prague, Czech Republic; 3Institute of Psychology, Academy of Sciences, Brno, Czech Republic; 4Department of Pediatric Neurology, Charles University Second Faculty of Medicine and University Hospital Motol, Prague, Czech Republic; 5Charles University First Faculty of Medicine, Prague, Czech Republic; 6Department of Psychology, Faculty of Arts, Masaryk University, Brno, Czech RepublicCorrespondence: Michal HrdlickaDepartment of Child Psychiatry, Charles University Second Faculty of Medicine, University Hospital Motol, V Uvalu 84, Prague 15006, Czech RepublicTel +420 224 433 400Fax +420 224 433 420Email michal.hrdlicka@lfmotol.cuni.czBackground: Diffusion tensor imaging (DTI) is a powerful tool for investigating brain anatomical connectivity. The aim of our study was to compare brain connectivity among children with autism spectrum disorders (ASD), developmental dysphasia (DD), and healthy controls (HC) in the following tracts: the arcuate fasciculus (AF), inferior frontal occipital fasciculus (IFOF), inferior longitudinal fasciculus (ILF), and uncinate fasciculus (UF).Methods: Our sample consisted of 113 children with a mean age 8.7±2.2 years (77 boys, 36 girls), divided into three subgroups: ASD (n=39), DD (n=36), and HC (n=38). The International Classification of Diseases, 10th ed. was used to make clinical diagnoses. DTI images were collected using a 1.5 T Phillips Achieva MR imaging system.Results: Detailed analyses of fractional anisotropy (FA) revealed significant differences among the ASD, DD, and HC groups in the left AF (p=0.014) and right AF (p=0.001), the left IFOF (p<0.001) and right IFOF (p<0.001), the left ILF (p<0.001) and right ILF (p<0.001), but not in the UF. Post-hoc analyses revealed three patterns of FA differences among the groups: (1) in the right AF, right IFOF, and right ILF, FA was significantly lower in the ASD group compared to the DD and HC groups; however, there was no difference in FA between DD and HC; (2) in the left AF and left IFOF, FA was significantly lower in the ASD than in the HC group, but there were no differences between DD vs HC nor DD vs ASD; and (3) in the left ILF, no difference in FA was seen between ASD and DD, but FA in both was significantly lower than in the HC.Conclusion: Microstructural white matter properties differed between ASD vs DD and HC subjects. The tract where FA impairment in ASD and DD subjects was the most similar was the left ILF.Keywords: autism, developmental dysphasia, magnetic resonance imaging, diffusion tensor imaging, tractography